Synthesis and characterization ofNickel doped ZnO thin Films on different substrate - Devapriya, D.; Sivakumar, S.; Rajeshkanna, G.; Kalaivanan, R.; Jayaprakash Shreedharan M.D, Dr T; M, Jeganathan (International Journal of Psychosocial Rehabilitation, 2018)
ZnO thin films are prepared from sol-gel of zinc acetateand by dip coating onto two different substrates: glass andaluminium foil. (i) Films on glass substrates. ZnO thin films with different concentrations of Ni2+ doping (0, 1, 5, 10 and 15 wt%) are prepared by the sol gel method. The film surface is with a ganglia-like structure as observed by Scanning Electron Microscopy (SEM). The films comprise of ZnOnanocrystallites with hexagonal crystal structure, as revealed by means of X-ray diffraction (XRD). (ii) Films on aluminium foil substrates. The ZnO films are annealed at different temperatures (100 °C, 300 °C and 500 °C) and characterized by means of SEM and XRD. The film surface is with the characteristic ganglia-like patterns. The crystalline structure is hexagonal with the crystallite sizes increasing with the annealing temperature.